Mothers Speak of the Effects of Terrorism on Children’s Education, Psychological Wellbeing, Mothers’ Strengths, and Resilience: A Qualitative Study - Bene, Konabe (Journal of Ecohumanism, 2025)
Terrorism has been an escalating major challenge that hindered the quality of life, including well-being, schooling, and local economic fabric. The existing knowledge base however suggests that mothers have not yet spoken enough of their accounts of terrorists’ activities on their families. The purpose of the present study was to gain insight into mothers’ versions of the impacts of terrorism on mothers and their progenies. To conduct this study, a multiphase thematic analysis was utilized to scrutinize qualitative data collected from 26 victimized mothers. Data were collected and analyzed until saturation was noticed. These data yielded contextual and individuals’ characteristics that mothers ascribed to terrorism. The following enriching and poignant themes emerged: disruption of education, increased dependency, behavior variations, psychological damages, financial struggles, and mothers’ strategies, strengths, and resilience. Results were discussed based on the Capability Approach framework, the existing findings, and mothers’ context-specific realities. It was furthermore suggested that future research should consider the mediated effects of social and economic-specific contexts on terrorism-related casualties to better understand its effects on the victimized mothers and their children. Recommendations were made for women and their children to benefit from near psychological services during the occurrence or absence of major traumatic events.